(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the aesthetic value of paralinguistics, which is one of the linguistic phenomena in the development of Uzbek literature, is scientifically and theoretically analyzed. In the study, the analytical effects of the genres of folklore such as lof, latifa, and askiya in the development of artistic works are based on the analysis of specific examples of Uzbek prose. The fact that the place and importance of folk dance in the development of modern Uzbek literature is incomparable is based on the theoretical opinions and scientific analyzes of world literary scholars and scholars of Uzbek literature. As a result of the scientific-theoretical analysis, the following conclusions are reached: In the study, the relationship of the genres of oral drama, askiya, lof, anecdote related to the public laughter with written prose, their spiritual significance in the genesis and artistic development of various genres of modern Uzbek literature in the shows made it possible to use materials in this direction. Linguistic effects of the culture of laughter in modern Uzbek literature, linguistic concepts, and the issue of speech culture in the research made it possible to use it as an important source in public holidays and events of our country.